2003
DOI: 10.1016/s1040-8428(02)00121-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between aging and carcinogenesis: a critical appraisal

Abstract: The incidence of cancer increases with age in humans and in laboratory animals alike. There are different patterns of age-related distribution of tumors in different organs and tissues. Aging may increase or decrease the susceptibility of various tissues to initiation of carcinogenesis and usually facilitates promotion and progression of carcinogenesis. Aging may predispose to cancer by several mechanisms: (1) tissue accumulation of cells in late stages of carcinogenesis; (2) alterations in homeostasis, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 236 publications
(213 reference statements)
1
61
0
2
Order By: Relevance
“…All these predictors are known for the relation with developing endometrial cancer (Smith et al, 2003;Beral et al, 2005;Lesko et al, 1985;Hinkula et al, 2002;Kitson et al, 2017). The relation between age and the development of several types of cancer has been most extensively described (DePinho, 2000;Balducci and Ershler, 2005;Anisimov, 2003). In the diagnostic models clinical predictors were more important, such as endometrial thickness, recurrent bleeding and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…All these predictors are known for the relation with developing endometrial cancer (Smith et al, 2003;Beral et al, 2005;Lesko et al, 1985;Hinkula et al, 2002;Kitson et al, 2017). The relation between age and the development of several types of cancer has been most extensively described (DePinho, 2000;Balducci and Ershler, 2005;Anisimov, 2003). In the diagnostic models clinical predictors were more important, such as endometrial thickness, recurrent bleeding and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are likely related to the fact that aging, in addition to prior exposure to chemotherapy and radiation, often facilitates carcinogenesis. [2,32,33] Previous research [34] reported that the prevalence of hypertension and diabetes among women is highest in the older age groups. The results in this study support the findings of Yancik et al [35] and Barbieri[36] that the prevalence of hypertension and diabetes actually begins to decline in the oldest age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, liver carcinoma cells transplanted into livers of young rats differentiate into hepatocytes; in contrast, when the same cells are transplanted into livers of old animals, these cells produce tumors consisting of undifferentiated cells [92]. In fact, agerelated changes in tissue environment substantially affect carcinogen induced tumorigenesis in many rodent model systems [93]. Moreover, one of the consequences of aging is the accumulation of senescent cells in many tissues [94][95][96], and senescent cells secrete a number of active molecules that can promote tumor growth [97,98].…”
Section: The Complex Relationship Between Aging Carcinogen Exposure mentioning
confidence: 99%